A needs-analysis on the engineering undergraduates' communication skills / Suzana Ab. Rahim - Ab. Rahim, Suzana (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2008)
With the recent development requiring the engineers of today to be endowed with soft skills; particularly in having the ability to communicate well, it is pertinent that the engineering undergraduates' needs towards being more conversant and their ability to communicate well be looked into. With that in mind, this study will look into the English Language communication skills required by the practising engineers at the work place. For the purpose of this study, the samples come from the engineering lecturers who have served as practising engineers so as to validate the work place requirements. The findings indicate that various language skills and language items are some of the areas need to be focused on and taught to the engineering undergraduates to further equip them with the essential package of being more marketable engineering graduates.